Identification of sawflies and horntails (Hymenoptera, 'Symphyta') through DNA barcodes: successes and caveats. (19th November 2016) - Schmidt, Stefan; Taeger, Andreas; Morinière, Jérôme; Liston, Andrew; Blank, Stephan M.; Kramp, Katja; Kraus, Manfred; Schmidt, Olga; Heibo, Erik; Prous, Marko; Nyman, Tommi; Malm, Tobias; et al.
Abstract: The 'Symphyta' is a paraphyletic assemblage at the base of the order Hymenoptera, comprising 14 families and about 8750 species. All have phytophagous larvae, except for the Orussidae, which are parasitoids. This study presents and evaluates the results of DNA barcoding of approximately 5360 specimens of 'Symphyta', mainly adults, and 4362 sequences covering 1037 species were deemed of suitable quality for inclusion in the analysis. All extant families are represented, except for the Anaxyelidae. The majority of species and specimens are from Europe, but approximately 38% of the species and 13% of the specimens are of non‐European origin. The utility of barcoding for species identification and taxonomy of 'Symphyta' is discussed on the basis of examples from each of the included families. A significant level of cryptic species diversity was apparent in many groups. Other attractive applications include the identification of immature stages without the need to rear them, community analyses based on metabarcoding of bulk samples and association of the sexes of adults.